Development of Android-Based Interactive Learning Media in a Surveying Quantity Course - Rahmi, Yulia; Arifin, Ari Syaiful Rahman (CIVED, 2024)
This study discusses the design and development of interactive Android-based learning media for the quantity surveying course for students in the field of building engineering education. Today's technological advancements necessitate innovation in educational media so that learning can be adapted to digital advancements and made more engaging in order for students to independently study the topic and comprehend the instructional medium. The purpose of this study is to evaluate the validity and practicality of interactive learning media based on Android in the quantitative surveying course. The DDD-E development model is used in this project's research and development (R&D) approach. Three experts validated the product, and 58 building engineering education students who did the surveying quantity course during the semester of January–June 2023 practiced their skills. According to the evaluation of interactive learning media based on Android that was done, the findings of the evaluation by material specialists were reached at 0.88 with a high validity category. The assessment of media experts obtained a score of 0.8 in the high validity category. The practicality assessment received a score of 0.80 in the high practicality category. Based on the results of the study, it can be concluded that the interactive learning media in the surveying quantity course made with the DDD-E research model can be said to be valid and practical with high categories and can be used in learning.